RESPON BEBERAPA VARIETAS KEDELAI (GLYCINE MAX (L.) MERRIL) TERHADAP INFEKSI PEANUT STRIPE POTYVIRUS - Hasriadi Mat Akin dan Muhammad Nurdin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2002)
Response of various soybean varieties [Glycine max (L.) Merril] againts peanut stripe potyvirus infection. This experiment was conducted to investigate the effect of PStV infection on soybean growth of various soybean varieties. Treatments were arranged in completely randomized design in split plot experiment with four replications. Main plots were virus-inoculated and uninoculated plants; subplots were eight soybean varieties (Wilis, Orba, MLG2521, Amerikana, Yellowbean, B3570, Slamet and Taichung). The results showed that infection decreased soybean growth indicated by reduction dry weight of soybean plant and reduction of soybean yield. Slamet variety compared to other varieties showed susceptible reaction indicated by the shortest incubation period (9,75 days), significant reduction of dry weigh of soybean plant, and the highest reduction of soybean yield (23,6%). Thaicung variety showed resistant reaction indicated by longest incubation period (14,3 days) and insignificant reduction of soybean growth and yield.